2009
DOI: 10.1016/j.jallcom.2009.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of In2O3 thin films prepared at various oxygen partial pressures

Abstract: a b s t r a c tPolycrystalline cubic In 2 O 3 thin films were deposited on the normal glass substrates by activated reactive evaporation method and systematically investigated the influence of oxygen partial pressure on the structural, optical, electrical and photoluminescence properties of the films. X-ray diffraction studies revealed that the films formed at oxygen partial pressure of 2 × 10 −3 mbar were nearly stoichiometric. The films formed at an oxygen partial pressure of 2 × 10 −3 mbar exhibited the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 31 publications
2
15
1
Order By: Relevance
“…In2O3-based TFTs are popular for high-resolution activematrix displays owing to its solution processing, which offers a scalable and cost-effective route for low-cost, equipment simplicity, high throughput, low material waste, and large-area deposition [3,22,23] compared to other deposition techniques, such as evaporation [24], sputtering [25], chemical vapor deposition [19,26], and atomic layer deposition [27,28]. In addition, the preparation of In2O3 thin films is entirely independent of 2methoxyethanol/acetonitrile-based liquid precursor solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In2O3-based TFTs are popular for high-resolution activematrix displays owing to its solution processing, which offers a scalable and cost-effective route for low-cost, equipment simplicity, high throughput, low material waste, and large-area deposition [3,22,23] compared to other deposition techniques, such as evaporation [24], sputtering [25], chemical vapor deposition [19,26], and atomic layer deposition [27,28]. In addition, the preparation of In2O3 thin films is entirely independent of 2methoxyethanol/acetonitrile-based liquid precursor solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the sensing properties of Ce 1− x M x O 2− δ (M = Ru, In) compounds are proposed to be studied for the first time, and are being compared with those ones mentioned for rare earth doped ceria and other simple oxides such as In 2 O 3 13, 31–37. Our hypothesis is that partial substitution of cerium by Ru or In to produce Ce 1− x Ru x O 2 and Ce 1− x In x O 2 solid solutions can lead to a defect‐like structure, increasing oxygen mobility, and additional electronic states which may be positive for their development as gas sensors.…”
Section: Introductionmentioning
confidence: 99%
“…5a,b. The SEM images revealed that the grains of as-deposited and annealed films are spherical in shape and are uniformly distributed over the entire film surface [60]. The size of the grain increases with increase of annealing temperature might be due to the increase in mobility of atoms [17,61].…”
Section: Morphological and Elemental Studymentioning
confidence: 99%